Pengaruh Kompetensi Pedagogik dan Kompetensi Profesional Guru Terhadap Kinerja Guru Sekolah Dasar di Kecamatan Secang Kabupaten Magelang - Ansori Budi Cahyana; Maximus Gorky Sembiring; Ety Syarifah (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract Teachers are the spearhead of the success of the education process in schools, so that in carrying out their duties, teachers are required to have complete and adequate competence. The mandatory competencies that a teacher must have to support their performance are pedagogic competence and professional competence. This study aims to analyze whether or not there is a relationship between pedagogic competence and professional competence with teacher performance. This research was conducted on elementary school teachers in Secang District, Magelang Regency with a population of 239 teachers. The sample used is the total population of 239 teachers. The independent variable in this study is pedagogic competence and professional competence, while the dependent variable is teacher performance. The measurement of the variables was carried out using a Likert scale. Data analysis was performed using multiple linear regression with the help of SPSS 22 software. From the regression coefficient values ​​for pedagogic competence and professional competence, multiple linear regression equations can be made as follows Y=26.185+0.350(X1)+0.549(X2)+e. Based on the results of the t-test, it was found that there is a relationship between pedagogic competence and teacher performance with a significance value of pedagogic competence variable of 0.000 < 0.05, there is a relationship between professional competence and teacher performance with a significance value of professional competence variable of 0.000 < 0.05. Based on the results of the F test, it was found that there was a relationship between pedagogic competence and professional competence together with the performance of elementary school teachers in Secang District, Magelang Regency with a significance value of 0.000 < 0.05 for the F test. The value of the coefficient of determination (R2) in this study was 45.2%, while the remaining 54.8% was influenced by other factors outside of this study. Keywords: Pedagogic Competence, Professional Competence, Teacher Performance